UNPACKING THE INVISIBLE MAN: READING THROUGH THE ANALYTIC OF INVISIBILITY, MONEY AND ROMANTICISM - Agarwal, Binoy Bhushan; Sinha, Rosy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the enduring imaginative appeal of The Invisible Man by Herbert George Wells, hereinafter referred to as H.G. Wells, through the trope of invisibility and money. In doing so, the paper also analyses the novel’s thematic concerns that reflects England’s transition amidst economic, social, and scientific changes. Further, it shall also elaborate on the intertwined conflict between Romantic ideals and urbanization in showcasing, the scientific hubris and the parochial attitudes of society, in exploring themes of literal, social, and psychological invisibility. Conclusively, it reads Wells’ novella as a cautionary tale signalling the dangers of unchecked ambition and underscores the need for ethical responsibility through the contrasting characters of Griffin and Dr. Kemp who highlight the potential for both harm and good in scientific endeavours.